The New Universal Library (London : International Learning Systems, 1969)
v. 1. A-AUG -- v. 2. AUK-BUF -- v. 3. BUG-COK -- v. 4. COL- DRI -- v. 5. DRO-FLY -- v. 6. v. 7. v. 8. v. 9. v. 10. v. 11. v. 12. v. 13. v. 14. v. 15.
Keywords: Encyclopedias and dictionaries